Produção de alfafa em função de espaçamentos e densidades - Bellettini, Silvestre; Rosolem, Ciro Antonio [UNESP]; Valério, Maria Apparecida (My University, 1997)
An experiment was conducted to study alfalfa (Medicago sativa L.) yields as affected by row spacings of 15, 20, 30 and 40 cm and plant densities originated from 10, 15, 20 and 30 kg/ha of seeds. The experiment was conducted on a Typic Eutrortox (Clay) in Bandeirantes, state of Paraná, Brazil. The experimetal design was a 4 × 4 factorial in randomized triplicated blocks. There was no significant effect of row spacings and plant populations on plant height and dry matter production. The 15 cm row spacing showed higher number of stems throughout the two years of the experiment. Up to the 6th cut the plant density of 30 kg/ha also lead to a higher number of stems/ha.

Com o objetivo de estudar a produção de alfafa (Medicago sativa L.) em espaçamentos de 15, 20, 30 e 40 cm entre linhas e densidades de 10, 15, 20 e 30 kg/ha de sementes, foi conduzido um experimento num Latossolo Roxo eutrófico, na Fundação Faculdade de Agronomia "Luiz Meneghel", em Bandeirantes, PR. O delineamento experimental foi em blocos ao acaso, com três repetições, em esquema fatorial 4 x 4. Não foi observado efeito significativo dos espaçamentos e densidades na altura das plantas nem na produção de matéria seca. Tampouco a interação foi significativa. O espaçamento de 15 cm foi o que apresentou maior número de caules em todos os cortes, o mesmo sendo observado para a densidade de 30 kg/ha de sementes até o 6o corte.
Alfalfa yield as affected by row spacing and plant population
Keywords: Dry matter; Medicago sativa; Population